Predictors of psychological functioning in children with cancer: disposition and cumulative life stressors. Issue 7 (1st August 2014) - Howard Sharp, Katianne M.; Rowe, Anjoli E.; Russell, Kathryn; Long, Alanna; Phipps, Sean
Abstract Objective This study examined psychological functioning in children with a history of cancer and a matched sample of healthy peers, while exploring the roles of disposition and stressful life events. Method Participants were 255 children with a history of cancer and 101 demographically matched children (8–17 years). Children completed measures of depression, anxiety, and posttraumatic stress symptoms (PTSS); history of stressful life events; and dispositional factors, including optimism and a five‐factor personality measure. Results Children with cancer did not differ from peers with regard to depression and PTSS, but reported significantly lower anxiety. In hierarchical regressions, children's depression, anxiety, and PTSS scores were largely predicted by dispositional variables and, to a lesser extent, stressful life events, after controlling for demographics and health status. Conclusion Children's psychological functioning is predicted primarily by disposition, and secondarily by history of stressful life events, with health status (i.e., cancer versus control) accounting for minimal, and often non‐significant variance in children's functioning. These findings further support that children with cancer are generally resilient, with factors predictive of their adjustment difficulties mirroring those of children without history of serious illness. Copyright © 2014 John Wiley & Sons, Ltd.